Breathlessness and cough in the acute setting - Marshall, Ben G. (Medicine (Abingdon), 2021)
The symptom of breathlessness is well recognized as part of the presentation of a wide range of medical conditions. It can be a manifestation of a life-threatening emergency. In acute medical settings, the priority is to quickly recognize patients who are critically unwell and require emergency treatment. For these patients, rapid initial assessment and immediate treatment are essential. However, once symptoms have stabilized or in less acute settings, a more thorough assessment is required. Cough is a common respiratory symptom, often part of a symptom complex, which is troublesome for the patient. It is important to recognize worrying associated features to prompt further investigation. In late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection emerged from a zoonotic source, resulting in many cases of infection, hospitalizations and deaths, and has since spread in a pandemic across every continent. A substantial percentage of patients with COVID-19 develop an acute respiratory illness requiring hospital care. Cough and acute breathlessness are two of the most prevalent symptoms in this infection; any patient presenting to an acute setting should currently be assumed to have this infection and immediately tested with a viral swab from the upper airway to guide management.